IDENTIFIKASI PROSES BERPIKIR KONSEPTUAL SISWA SMP MELALUI METODE MIND MAPPING - Dwi Noviani Sulisawati; Eric Dwi Putra (Program Studi Pendidikan Matematika, 2020)
The importance of emphasizing material understanding, creativity, freedom of expression, and teachers 'understanding of the thinking processes of their students, so with this research, the researcher wants to provide an overview of junior high school students' thinking processes through the mind mapping method which is carried out on 3 subjects with different mathematical abilities. Subjects were selected by purposive sampling according to predetermined criteria. The data was collected using the test method in the form of giving the task of making concept maps about the material being taught by the teacher and interviews about the results of their work. Furthermore, the data was processed using qualitative data analysis which includes reduction, data presentation, and drawing conclusions. From the analysis, it was found that students with high abilities could fulfill 8 of the 9 indicators. For students with moderate ability, they can meet 7 of the 9 indicators proposed, while students with low abilities were only able to meet 6 of the 9 indicators. But in terms of using colors, students with low abilities were able to use more color variations with gradation techniques. Further research can take other subjects with various variables that are able to support students' thinking processes.